The Structure and Kinematics of the Galaxy Thin Gaseous Disk Outside the Solar Orbit. (4th January 2016) - Galazutdinov, G.; Strobel, A.; Musaev, F. A.; Bondar, A.; Krełowski, J.
Abstract: The rotation curve of the Galaxy is generally thought to be flat. However, using radial velocities from interstellar molecular clouds, as is common in rotation curve determination, seems to be incorrect and may lead to wrongly inferring that the rotation curve is flat indeed. Tests based on photometric and spectral observations of bright stars may also be misleading. The rotation tracers (OB stars) are affected by motions around local gravity centers and by pulsation effects seen in such early-type objects. To get rid of the latter involves extensive observing work. We introduce a method of studying the kinematics of the thin disk of our Galaxy outside the solar orbit in a way that avoids these problems. We propose a test based on observations of interstellar Caii H and K lines that determines both radial velocities and distances. We implemented the test using stellar spectra of thin disk stars at Galactic longitudes of 135° and 180°. Using this method, we constructed the rotation curve of the thin disk of the Galaxy. The test leads to the obvious conclusion that the rotation curve of the thin gaseous galactic disk, represented by the Caii lines, is Keplerian outside the solar orbit rather than flat.